The Role Of The Women's Empowerment, Child Protection And Community Empowerment Service (DP3APM) Of Pekanbaru City In Advocacy For Victims In Fulfilling The Rights To Child Support - Lestari, Ria; Zulherawan, M. (Doctoral Program of Social Science Pasundan University, 2025)
The increasing number of divorce cases in Indonesia has a serious impact on the fulfillment of children's rights to support, which should remain the responsibility of parents, especially fathers, even though the marriage has ended. This study aims to examine the strategic role of the Pekanbaru City Women's Empowerment, Child Protection and Community Empowerment Service (DP3APM) in advocating for children who are victims of violations of the right to support. Using a qualitative descriptive approach and a victimology approach, this study explores the function of DP3APM as a regulator, dynamic, and facilitator in order to ensure the protection and fulfillment of children's basic rights after divorce. Data were obtained through in-depth interviews, observations, and documentation of relevant informants, such as DP3APM staff, legal counselors, psychologists, and mothers/guardians of victimized children. The results of the study show that DP3APM not only plays a role in formulating policies, but is also active in providing legal assistance, psychosocial, and mediation services between parties. Despite facing structural and cultural challenges, DP3APM has succeeded in becoming a key institution in bridging children's rights with real access to justice. These findings underscore the importance of integrating legal, social, and psychological approaches in state institution-based advocacy efforts. The Pekanbaru DP3APM work model can be a reference for other regions facing similar problems.